Elastic-Plastic Plates Sealing a Liquid; Tests and Analysis - Sokół-Supel, J.; Supel, J.A.; Guerlement, G. (Engineering Transactions, 1995)
Circular steel plates sealing the vessels containing compressible liquid are considered. The edge of the plate is built into the vessel wall. The plate is loaded at its central part and supported by the liquid pressure. The material is assumed to be elastic-perfectly plastic, obeying the Tresca yield criterion and the associated flow rule. A closed-form analytical solution is obtained in the case of monotonically increasing load. The corresponding experimental study is aimed at verification of the analytical approach. Special attention is given to the evolution of the apparent compressibility of the liquid due to air residuals and to the deformations of the lateral walls of the vessel.